Corporate accreditation system of PJSC Gazprom as a tool for ensuring uniformity of measurements of organization - R. T. Saetova; I. A. Battalov; Ya. V. Denisova (Омский научный вестник)
The relevance of the research is predetermined by factors as the strengthening of the role of chemical analytical (testing) laboratories of gas transmission companies in the implementation of Gazprom’s PJSC strategy in the field of reliable and trouble-free transportation of natural gas and the need of testing laboratories to constantly confirm their impartiality and ability to carry out production tasks at a competent level. Protection of the interests of the consumer and the rights of the supplier is ensured by the accuracy of determining the quantity and quality indicators of the supplied products established in technical regulations, standards and by minimizing risks to life, human health and the environment on the basis of reliable measurements. The issue of the quality of measurement results is acute today. Depending on the direction of measurement processes and applications of the measurement results the shape of laboratories attestation has different requirements. All types of measurements carried out in an organization should be subject to mandatory or voluntary accreditation. Ensuring the competence of chemical analytical laboratories at Gazprom PJSC subsidiaries and companies of in the field of product conformity assessment is facilitated by the corporate accreditation system operating in accordance with Company Standard STO Gazprom 5.8-2020. Uniform requirements adapted to the industry specifics of activities and sufficient for reliable measurement results, encourage subsidiaries to become participants in the updated accreditation system. Gazprom Transgaz Kazan LLC acts as the research base. The object of the study is to ensure the uniformity of measurements through compliance with the accreditation criteria, the subject is the accreditation of a testing laboratory in the corporate system. The article considers the procedure and activities carried out by the testing laboratory during accreditation.